Molding for medical use
A polycarbonate resin with specific plant-derived structural units addresses nucleic acid adsorption issues, enhancing analytical efficiency and reducing contamination in medical containers.
Patent Information
- Application Number
- JP2023120008
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-24
- Publication Date
- 2025-02-05
AI Technical Summary
Existing materials used for handling nucleic acids in medical applications suffer from adsorption issues, leading to decreased analytical efficiency and increased errors, and do not adequately address contamination or elution of impurities, while also being non-sustainable due to petroleum-based resources.
A medical molding body composed of polycarbonate resin containing specific structural units derived from plant-based dihydroxy compounds, such as isosorbide, and aliphatic or cycloaliphatic dihydroxy compounds, which suppress nucleic acid adsorption and enhance impact resistance and transparency.
The proposed solution effectively reduces nucleic acid adsorption, improves impact strength and transparency, and prevents contamination, making it suitable for medical containers like vials, ampoules, and syringes.
Smart Images

Figure 2025017116000001 
Figure 2025017116000002 
Figure 2025017116000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a molded article for medical use. [Background technology]
[0002] With the development of the bioindustry, the industrial use of nucleic acids has become widespread in the food, medical, and chemical industries, etc. In these industrial fields, nucleic acids are sometimes used for microscopic observation, and various products made of transparent plastics with excellent visibility are used to handle nucleic acids.
[0003] Nucleic acids are often handled in minute amounts, for example, on the order of micrograms. In recent years, advances in analytical technology have led to a demand for handling even smaller amounts of nucleic acid, for example, on the order of nanograms or picograms. In such fields, the adsorption of nucleic acids to the surfaces of plastic products causes problems such as reduced analytical efficiency and increased analytical errors.
[0004] In order to suppress the adsorption of nucleic acids, plastics to which polymers with low surface energy such as siloxane have been added have been proposed (see Patent Document 1). In addition, methods have been proposed in which secondary processing is performed on the surface of plastics to impart biocompatibility or suppress the adsorption of biological components (see Patent Documents 2 and 3). However, these methods have not been able to solve problems such as contamination and the elution of impurities. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2022-64159 A [Patent Document 2] JP 2014-161675 A [Patent Document 3] Patent Publication No. 2021-91908 Summary of the Invention [Problem to be solved by the invention]
[0006] In recent years, there has been concern about global warming due to the depletion of petroleum resources and the increase in carbon dioxide emissions, and so there is a demand for materials made from plant-derived monomers. In addition, as the development of nucleic acid medicines containing DNA and RNA progresses, it is desirable for medical molded products such as vials, ampoules, tubes, syringes, and medical bottles to suppress the adsorption of nucleic acids. Furthermore, since medical molded products may be scratched or cracked due to impacts during transportation, excellent impact resistance and scratch resistance are desired.
[0007] The present invention has been made in consideration of the above background, and aims to provide a medical molded article that is made from plant-derived materials, is capable of suppressing adsorption of nucleic acids, and has excellent impact strength, scratch resistance, and transparency. [Means for solving the problem]
[0008] That is, the present invention has the following aspects. [1] A medical molded article containing a polycarbonate resin, The polycarbonate resin contains a structural unit (A) derived from a dihydroxy compound represented by the following formula (1) and a structural unit (B) derived from an aliphatic dihydroxy compound and / or an alicyclic dihydroxy compound, The amount of nucleic acid adsorbed was 4.0ng / mm 2 The medical molded article is as follows:
[0009] [ka]
[0010] [2] The molded article for medical use according to [1], wherein the content of the structural unit (A) is 30 to 95 mol % based on all structural units derived from dihydroxy compounds in the polycarbonate resin. [3] The medical molded article according to [1] or [2], wherein the reduced viscosity of the polycarbonate resin is 0.30 dL / g or more and less than 0.70 dL / g. [4] The molded article for medical use according to any one of [1] to [3], which has a shape of a vial, an ampule, a tube, a syringe, or a bottle. Effect of the Invention
[0011] The medical molded body is made of plant-derived raw materials, and is capable of suppressing the adsorption of nucleic acids, and is excellent in impact strength, scratch resistance, and transparency. In addition, since the constituent materials of the medical molded body exhibit the effect of suppressing the adsorption of nucleic acids, there is no need to provide a coating for suppressing the adsorption of nucleic acids, and contamination can be prevented. Therefore, the medical molded body is suitable for medical vials, ampoules, tubes, syringes, bottles, etc. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The embodiment of the present invention will be described in detail below, but the description of the configuration described below is one example (i.e., a representative example) of the embodiment of the present invention, and the present invention is not limited to the following content as long as it does not exceed the gist of the present invention. In this specification, the term "structural unit" refers to a partial structure constituting a resin, and a specific partial structure contained in a repeating structural unit. For example, it refers to a partial structure sandwiched between adjacent linking groups in a resin, or a partial structure sandwiched between a polymerizable reactive group present at the end of a polymer and a linking group adjacent to the polymerizable reactive group. More specifically, in the case of a polycarbonate resin, a carbonyl group is a linking group, and a partial structure sandwiched between adjacent carbonyl groups is called a structural unit. In addition, when the expression "~" is used in this specification, it is used in a sense including the numerical value or physical value described before and after it. In addition, the numerical value or physical value described as the upper limit and lower limit is used in a sense including the value. In addition, "parts by weight" and "parts by mass", "% by weight" and "% by mass" are substantially synonymous.
[0013] [Polycarbonate resin] (Dihydroxy Compounds) The polycarbonate resin contains a structural unit (A) derived from a dihydroxy compound represented by the following formula (1) and a structural unit (B) derived from an aliphatic dihydroxy compound and / or an alicyclic dihydroxy compound. In other words, the polycarbonate resin is a copolymer polycarbonate, which is a copolymer in which at least the dihydroxy compound represented by formula (1) and an aliphatic dihydroxy compound and / or an alicyclic dihydroxy compound are copolymerized. Examples of the polycarbonate resin include copolymers of the dihydroxy compound represented by formula (1) and an aliphatic dihydroxy compound and / or an alicyclic dihydroxy compound. In polycarbonate resin, the structural unit (A) and the structural unit (B) are different. The dihydroxy compound forming the structural unit (A) is appropriately referred to as the "first compound", and the dihydroxy compound forming the structural unit (B) is appropriately referred to as the "second compound". Since the polycarbonate resin has the structural unit (A) derived from the dihydroxy compound represented by formula (1), the molded article made of the polycarbonate resin has low adsorption of nucleic acids, excellent impact resistance, and excellent transparency. [ka]
[0014] Examples of the first compound include isosorbide, isomannide, and isoidite, which are stereoisomers. These may be used alone or in combination of two or more. Among these first compounds, isosorbide is the most preferable from the viewpoints of availability, ease of production, and moldability. Isosorbide is obtained by dehydration condensation of sorbitol, which is abundant as a plant-derived resource and is produced from various starches that are easily available.
[0015] The structural unit (B) is a structural unit derived from an aliphatic dihydroxy compound and / or an alicyclic dihydroxy compound, and is a structural unit derived from a second compound. The structural unit (B) is preferably a structural unit derived from an aliphatic dihydroxy compound or an alicyclic dihydroxy compound, and more preferably a structural unit derived from an alicyclic dihydroxy compound.
[0016] Examples of the aliphatic dihydroxy compound include straight-chain aliphatic dihydroxy compounds such as ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, and 1,12-dodecanediol; and branched-chain aliphatic dihydroxy compounds such as 1,2-propanediol, 1,3-butanediol, 1,2-butanediol, neopentyl glycol, and hexylene glycol.
[0017] Examples of the alicyclic dihydroxy compound include dihydroxy compounds which are primary alcohols of alicyclic hydrocarbons, such as dihydroxy compounds derived from terpene compounds, such as 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, tricyclodecane dimethanol, pentacyclopentadecane dimethanol, 2,6-decalin dimethanol, 1,5-decalin dimethanol, 2,3-decalin dimethanol, 2,3-norbornane dimethanol, 2,5-norbornane dimethanol, 1,3-adamantanedimethanol, and limonene; and dihydroxy compounds which are secondary or tertiary alcohols of alicyclic hydrocarbons, such as 1,2-cyclohexanediol, 1,4-cyclohexanediol, 1,3-adamantanediol, hydrogenated bisphenol A, and 2,2,4,4-tetramethyl-1,3-cyclobutanediol. The alicyclic dihydroxy compound is preferably at least one selected from the group consisting of a compound having a carbon skeleton of a cyclic structure having 3 to 8 carbon atoms (specifically, a cycloalkane structure having 3 to 8 carbon atoms) such as cyclohexanedimethanol, a compound having a tricyclodecane skeleton such as tricyclodecanedimethanol, and a compound having a norbornane skeleton such as norbornanedimethanol, and more preferably a compound having a carbon skeleton of a cyclic structure having 3 to 8 carbon atoms (specifically, a cycloalkane structure having 3 to 8 carbon atoms) and / or a compound having a tricyclodecane skeleton. In addition, the number of carbon atoms in the cycloalkane in the dihydroxy compound having a cycloalkane structure (specifically, a dihydroxycycloalkane) is more preferably 4 to 6.
[0018] From the viewpoint of further improving the nucleic acid adsorption inhibitory effect and impact resistance, the second compound is preferably cyclobutanediol or cyclohexanedimethanol. These compounds have similar molecular structures, and copolymer polycarbonates of cyclobutanediol and / or cyclohexanedimethanol with the first compound exhibit similar physical properties and characteristics.
[0019] From the viewpoint of further reducing the amount of nucleic acid adsorbed when nucleic acid is adsorbed to a molded product and further improving transparency, the content ratio of the structural unit (A) in the polycarbonate resin is preferably 30 mol% to 95 mol%, more preferably 55 mol% to 95 mol%, and even more preferably 65 mol% to 90 mol%, based on all structural units derived from dihydroxy compounds constituting the polycarbonate resin. In addition, if the content ratio of the structural unit (A) is increased within the above range, the composition ratio from plant-derived raw materials increases, which is advantageous from the viewpoint of carbon neutrality.
[0020] The content ratio of the structural unit (B) in the polycarbonate resin is preferably 5 mol % to 45 mol %, more preferably 7 mol % to 40 mol %, and further preferably 10 mol % to 35 mol %, based on all structural units derived from dihydroxy compounds.
[0021] (Other dihydroxy compounds) The polycarbonate resin may further contain structural units derived from other dihydroxy compounds in addition to the structural units (A) and (B). Examples of the other dihydroxy compounds include aromatic dihydroxy compounds. Examples of aromatic dihydroxy compounds include substituted or unsubstituted bisphenol compounds. Specifically, bis(4-hydroxyphenyl)methane, 1,1-bis(4-hydroxyphenyl)ethane, 1,1-bis(4-hydroxyphenyl)propane, 2,2-bis(4-hydroxyphenyl)propane, 1,1-bis(4-hydroxyphenyl)butane, 2,2-bis(4-hydroxyphenyl)butane, 1,1-bis(4-hydroxyphenyl)pentane, 2,2-bis(4-hydroxyphenyl)pentane, 3,3-bis(4-hydroxyphenyl)pentane, 2,2-bis(4-hydroxyphenyl)-3-methylbutane, 1,1-bis(4-hydroxyphenyl)hexane, 2,2-bis(4-hydroxyphenyl) Bisphenol compounds having no substituents on the aromatic ring, such as hexane, 3,3-bis(4-hydroxyphenyl)hexane, 2,2-bis(4-hydroxyphenyl)-4-methylpentane, 1,1-bis(4-hydroxyphenyl)cyclopentane, and 1,1-bis(4-hydroxyphenyl)cyclohexane; bisphenol compounds having an aryl group as a substituent on the aromatic ring, such as bis(3-phenyl-4-hydroxyphenyl)methane, 1,1-bis(3-phenyl-4-hydroxyphenyl)ethane, 1,1-bis(3-phenyl-4-hydroxyphenyl)propane, and 2,2-bis(3-phenyl-4-hydroxyphenyl)propane;Bis(4-hydroxy-3-methylphenyl)methane, 1,1-bis(4-hydroxy-3-methylphenyl)ethane, 1,1-bis(4-hydroxy-3-methylphenyl)propane, 2,2-bis(4-hydroxy-3-methylphenyl)propane, 1,1-bis(4-hydroxy-3-methylphenyl)cyclohexane, bis(4-hydroxy-3-ethylphenyl)methane, 1,1-bis(4-hydroxy-3-ethylphenyl)ethane, 1,1-bis( 4-hydroxy-3-ethylphenyl)propane, 2,2-bis(4-hydroxy-3-ethylphenyl)propane, 1,1-bis(4-hydroxy-3-ethylphenyl)cyclohexane, 2,2-bis(4-hydroxy-3-isopropylphenyl)propane, 2,2-bis(4-hydroxy-3-(sec-butyl)phenyl)propane, bis(4-hydroxy-3,5-dimethylphenyl)methane, 1,1-bis(4-hydroxy-3,5-dimethylphenyl) bisphenol compounds having an alkyl group as a substituent on an aromatic ring, such as 2,2-bis(4-hydroxy-3,5-dimethylphenyl)ethane, 2,2-bis(4-hydroxy-3,5-dimethylphenyl)propane, 1,1-bis(4-hydroxy-3,5-dimethylphenyl)cyclohexane, bis(4-hydroxy-3,6-dimethylphenyl)methane, 1,1-bis(4-hydroxy-3,6-dimethylphenyl)ethane, 2,2-bis(4-hydroxy-3,6-dimethylphenyl)propane, bis(4-hydroxy-2,3,5-trimethylphenyl)methane, 1,1-bis(4-hydroxy-2,3,5-trimethylphenyl)ethane, 2,2-bis(4-hydroxy-2,3,5-trimethylphenyl)propane, bis(4-hydroxy-2,3,5-trimethylphenyl)phenylmethane, 1,1-bis(4-hydroxy-2,3,5-trimethylphenyl)phenylethane, and 1,1-bis(4-hydroxy-2,3,5-trimethylphenyl)cyclohexane;Examples of such bisphenol compounds include bis(4-hydroxyphenyl)phenylmethane, 1,1-bis(4-hydroxyphenyl)-1-phenylethane, 1,1-bis(4-hydroxyphenyl)-1-phenylpropane, bis(4-hydroxyphenyl)diphenylmethane, and bis(4-hydroxyphenyl)dibenzylmethane, in which a divalent group linking aromatic rings has an aryl group as a substituent; bisphenol compounds in which aromatic rings are linked by ether bonds, such as 4,4'-dihydroxydiphenyl ether and 3,3',5,5'-tetramethyl-4,4'-dihydroxydiphenyl ether; bisphenol compounds in which aromatic rings are linked by sulfone bonds, such as 4,4'-dihydroxydiphenyl sulfone and 3,3',5,5'-tetramethyl-4,4'-dihydroxydiphenyl sulfone; and bisphenol compounds in which aromatic rings are linked by sulfide bonds, such as 4,4'-dihydroxydiphenyl sulfide and 3,3',5,5'-tetramethyl-4,4'-dihydroxydiphenyl sulfide. As the other dihydroxy compounds (specifically, aromatic dihydroxy compounds), one type may be used alone, or two or more types may be used in combination.
[0022] From the viewpoint of further improving heat resistance, impact resistance, moldability, etc. while maintaining a high level of transparency, the content of the structural unit derived from the aromatic dihydroxy compound constituting the polycarbonate resin is preferably 0 mol% or more and less than 1 mol%, more preferably 0 mol% or more and less than 0.8 mol%, and even more preferably 0 mol% or more and less than 0.5 mol% relative to the structural units derived from all dihydroxy compounds constituting the polycarbonate resin. By including a structural unit derived from an aromatic dihydroxy compound in the polycarbonate resin, improvements in heat resistance, impact resistance, moldability, etc. can be expected. From the viewpoint of further improving transparency, it is even more preferable that the content of the structural unit derived from the aromatic dihydroxy compound in the polycarbonate resin is 0 (mol%), and it is particularly preferable that the polycarbonate resin has only the structural unit (A) derived from the dihydroxy compound represented by formula (1) and the structural unit (B) derived from an aliphatic dihydroxy compound and / or an alicyclic dihydroxy compound as the structural unit derived from the dihydroxy compound. From the viewpoint of further improving the transparency and impact resistance of the medical molded article, the polycarbonate resin is most preferably a copolymer of a dihydroxy compound represented by formula (1) and an alicyclic dihydroxy compound.
[0023] (carbonic acid diester) The polycarbonate resin can be obtained by polycondensing a dihydroxy compound including the above-mentioned dihydroxy compound and a carbonic acid diester as raw materials through an ester exchange reaction. The carbonic acid diester may usually be one represented by the following formula (2): These carbonic acid diesters may be used alone or in combination of two or more.
[0024] [ka]
[0025] In formula (2), A 1 and A 2each independently represents a substituted or unsubstituted aliphatic group having 1 to 18 carbon atoms, or a substituted or unsubstituted aromatic group. Examples of the carbonic acid diester represented by formula (2) include diphenyl carbonate, substituted diphenyl carbonate such as ditolyl carbonate, dimethyl carbonate, diethyl carbonate, di-t-butyl carbonate, etc. Diphenyl carbonate and substituted diphenyl carbonate are preferred, and diphenyl carbonate is more preferred. The carbonic acid diester may contain impurities such as chloride ions. The impurities contained may inhibit the polycondensation reaction or deteriorate the color tone of the resulting polycarbonate resin. Therefore, it is preferable to use the carbonic acid diester after purifying it by distillation or the like, as necessary. The carbonic acid diester may contain impurities such as chloride ions, which may inhibit the polymerization reaction or may cause the resulting polycarbonate resin to have a yellowish color, resulting in a deteriorated hue. Therefore, it is preferable to use the carbonic acid diester purified by distillation or the like, as necessary.
[0026] The carbonic acid diester is preferably used in a molar ratio of 0.90 to 1.20, more preferably in a molar ratio of 0.95 to 1.10, even more preferably in a molar ratio of 0.96 to 1.10, and even more preferably in a molar ratio of 0.98 to 1.04, relative to the total dihydroxy compounds used in the melt polymerization. By setting the molar ratio to the lower limit or more of the above range, the increase in the terminal hydroxyl group of the polycarbonate resin is suppressed, the thermal stability of the polymer is improved, coloring during molding of the polycarbonate resin is more prevented, the transesterification reaction rate is improved, and the desired high molecular weight product is more easily obtained. In addition, by setting the molar ratio to the upper limit or less of the above range, the transesterification reaction rate under the same conditions is improved, and the production of a polycarbonate resin with a desired molecular weight is facilitated. Furthermore, the amount of residual carbonic acid diester in the polycarbonate resin produced can be reduced. Residual carbonic acid diester may be undesirable as it may cause odor during molding or in the molded product, and may also increase the heat history during the polymerization reaction, deteriorating the properties of the polycarbonate resin, such as weather resistance.
[0027] The concentration of the residual carbonate diester in the polycarbonate resin is preferably 200 ppm by weight or less, more preferably 100 ppm by weight or less, even more preferably 60 ppm by weight or less, and even more preferably 30 ppm by weight or less. In this case, ultraviolet light absorption by the residual carbonate diester is suppressed, and the light resistance of the polycarbonate resin is further improved. It is difficult to completely remove the carbonate diester from the polycarbonate resin, and the polycarbonate resin may contain unreacted carbonate diester. The lower limit of the concentration of the unreacted carbonate diester in the polycarbonate resin is usually 1 ppm by weight.
[0028] (Transesterification catalyst) The polycarbonate resin is produced by transesterification of a dihydroxy compound including a first dihydroxy compound and a second dihydroxy compound with a carbonic acid diester represented by formula (2). More specifically, the polycarbonate resin is obtained by removing the monohydroxy compound and the like produced as by-products by the transesterification reaction from the system. In the transesterification reaction, melt polymerization is usually carried out in the presence of a transesterification catalyst.
[0029] Examples of the transesterification catalyst (hereinafter referred to as "catalyst" where appropriate) include basic compounds such as metal compounds of Group I or Group II (hereinafter referred to as "Group 1" and "Group 2", respectively) in the long-form periodic table, basic boron compounds, basic phosphorus compounds, basic ammonium compounds, and amine compounds. Among these, Group 1 metal compounds and / or Group 2 metal compounds are preferably used.
[0030] It is also possible to use auxiliary basic compounds such as basic boron compounds, basic phosphorus compounds, basic ammonium compounds, amine compounds, etc. together with the Group 1 metal compounds and / or Group 2 metal compounds. It is preferable to use only the Group 1 metal compounds and / or Group 2 metal compounds. The Group 1 metal compound and / or Group 2 metal compound is usually used in the form of a hydroxide or a salt such as a carbonate, carboxylate or phenol salt. From the viewpoints of availability and ease of handling, the hydroxide, carbonate or acetate is preferred, and from the viewpoints of preventing deterioration in the hue of the polycarbonate resin and polymerization activity, the acetate is preferred.
[0031] Examples of Group 1 metal compounds include sodium hydroxide, potassium hydroxide, lithium hydroxide, cesium hydroxide, sodium hydrogen carbonate, potassium hydrogen carbonate, lithium hydrogen carbonate, cesium hydrogen carbonate, sodium carbonate, potassium carbonate, lithium carbonate, cesium carbonate, sodium acetate, potassium acetate, lithium acetate, cesium acetate, sodium stearate, potassium stearate, lithium stearate, cesium stearate, sodium borohydride, potassium borohydride, lithium borohydride, cesium borohydride, sodium phenyl borohydride, and phenyl borohydride. Examples of suitable phenylborates include potassium boron phenylide, lithium boron phenylide, cesium phenylide, sodium benzoate, potassium benzoate, lithium benzoate, cesium benzoate, disodium hydrogen phosphate, dipotassium hydrogen phosphate, dilithium hydrogen phosphate, dicesium hydrogen phosphate, disodium phenylphosphate, dipotassium phenylphosphate, dilithium phenylphosphate, dicesium phenylphosphate, sodium, potassium, lithium, and cesium alcoholates and phenolates, and the disodium, dipotassium, dilithium, and dicesium salts of bisphenol A. Among these, cesium compounds and lithium compounds are preferred.
[0032] Examples of Group 2 metal compounds include calcium hydroxide, barium hydroxide, magnesium hydroxide, strontium hydroxide, calcium hydrogen carbonate, barium hydrogen carbonate, magnesium hydrogen carbonate, strontium hydrogen carbonate, calcium carbonate, barium carbonate, magnesium carbonate, strontium carbonate, calcium acetate, barium acetate, magnesium acetate, strontium acetate, calcium stearate, barium stearate, magnesium stearate, strontium stearate, etc. Among these, magnesium compounds, calcium compounds, and barium compounds are preferred, and magnesium compounds and / or calcium compounds are more preferred.
[0033] Examples of basic boron compounds include sodium salts, potassium salts, lithium salts, calcium salts, barium salts, magnesium salts, and strontium salts of tetramethyl boron, tetraethyl boron, tetrapropyl boron, tetrabutyl boron, trimethylethyl boron, trimethylbenzyl boron, trimethylphenyl boron, triethylmethyl boron, triethylbenzyl boron, triethylphenyl boron, tributylbenzyl boron, tributylphenyl boron, tetraphenyl boron, benzyltriphenyl boron, methyltriphenyl boron, and butyltriphenyl boron.
[0034] Examples of basic phosphorus compounds include triethylphosphine, tri-n-propylphosphine, triisopropylphosphine, tri-n-butylphosphine, triphenylphosphine, tributylphosphine, and quaternary phosphonium salts. Examples of basic ammonium compounds include tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, trimethylethylammonium hydroxide, trimethylbenzylammonium hydroxide, trimethylphenylammonium hydroxide, triethylmethylammonium hydroxide, triethylbenzylammonium hydroxide, triethylphenylammonium hydroxide, tributylbenzylammonium hydroxide, tributylphenylammonium hydroxide, tetraphenylammonium hydroxide, benzyltriphenylammonium hydroxide, methyltriphenylammonium hydroxide, and butyltriphenylammonium hydroxide.
[0035] Examples of amine compounds include 4-aminopyridine, 2-aminopyridine, N,N-dimethyl-4-aminopyridine, 4-diethylaminopyridine, 2-hydroxypyridine, 2-methoxypyridine, 4-methoxypyridine, 2-dimethylaminoimidazole, 2-methoxyimidazole, imidazole, 2-mercaptoimidazole, 2-methylimidazole, and aminoquinoline.
[0036] Among the above, it is preferable to use at least one metal compound selected from the group consisting of Group 2 metal compounds and lithium compounds as a catalyst, which can further improve various physical properties such as transparency, hue, and light resistance of the polycarbonate resin. From the viewpoint of further improving the transparency, hue, and light resistance of the polycarbonate resin, the catalyst is more preferably at least one metal compound selected from the group consisting of magnesium compounds and calcium compounds.
[0037] When the catalyst is a Group 1 metal compound and / or a Group 2 metal compound, the amount of the catalyst used, calculated as the metal amount, is preferably 0.1 to 300 μmol, more preferably 0.1 to 100 μmol, even more preferably 0.5 to 50 μmol, and even more preferably 1 to 25 μmol, per mole of the total dihydroxy compounds to be subjected to the reaction. When the catalyst is a compound containing at least one metal selected from the group consisting of lithium and group 2 metals, particularly when the catalyst is a magnesium compound and / or a calcium compound, the lower limit of the amount of catalyst used is preferably 0.1 μmol, more preferably 0.5 μmol, and even more preferably 0.7 μmol, calculated as metal, relative to 1 mole of all dihydroxy compounds used in the reaction, and the upper limit is preferably 20 μmol, more preferably 10 μmol, more preferably 3 μmol, and even more preferably 2 μmol, calculated as metal, relative to 1 mole of all dihydroxy compounds used in the reaction.
[0038] By setting the amount of catalyst to the lower limit or more within the above range, the polymerization activity required to produce a polycarbonate resin with a desired molecular weight is obtained, and sufficient fracture energy is obtained. On the other hand, by setting the amount of catalyst to the upper limit or less within the above range, the color of the resulting polycarbonate resin is improved and the generation of by-products can be suppressed. Furthermore, the fluidity is improved, the generation of gel is suppressed, and brittle fracture is less likely to occur. This makes it easier to produce the targeted high-quality polycarbonate resin.
[0039] <Production method of polycarbonate resin> The polycarbonate resin is obtained by melt-polymerizing a dihydroxy compound including a first dihydroxy compound and a second dihydroxy compound with a carbonic acid diester through a transesterification reaction. The dihydroxy compound and the carbonic acid diester are preferably mixed uniformly before the transesterification reaction.
[0040] The mixing temperature is usually 80°C or higher. From the viewpoints of improving the dissolution rate, sufficiently increasing the solubility, and avoiding problems such as solidification, the mixing temperature is preferably 90°C or higher. On the other hand, the mixing temperature is usually 250°C or lower. From the viewpoints of more reliably avoiding thermal deterioration of the dihydroxy compound, improving the hue of the obtained polycarbonate resin, and improving the light resistance, the mixing temperature is preferably 200°C or lower, more preferably 150°C or lower. The mixing temperature is further preferably 100°C or higher and 120°C or lower.
[0041] The dihydroxy compound and the carbonic acid diester are melted or mixed in an atmosphere with an oxygen concentration within a predetermined range. The oxygen concentration is preferably 10% by volume or less. More preferably, the oxygen concentration is 0.0001% by volume to 10% by volume, even more preferably, 0.0001% by volume to 5% by volume, and even more preferably, 0.0001% by volume to 1% by volume. In this case, the color of the polycarbonate resin becomes better.
[0042] The polycarbonate resin is preferably produced by melt polymerization in multiple stages using a catalyst and multiple reactors. The reason for carrying out melt polymerization in multiple reactors is that in the early stage of the melt polymerization reaction, since the monomer contained in the reaction liquid is large, it is important to suppress the volatilization of the monomer while maintaining the required polymerization rate, and in the later stage of the melt polymerization reaction, it is important to sufficiently distill off the by-product monohydroxy compound in order to shift the equilibrium to the polymerization side. In this way, in order to set different polymerization reaction conditions, it is preferable to use multiple reactors arranged in series from the viewpoint of production efficiency. As described above, the number of the reactors may be at least two or more, but from the viewpoint of production efficiency, it is preferable to use three or more, more preferably three to five, and even more preferably four.
[0043] The reaction may be carried out in any of a batch system, a continuous system, or a combination of a batch system and a continuous system. In order to suppress the amount of monomer distilled off, it is effective to use a reflux condenser in the polymerization reactor, and this effect is particularly large in a reactor in the early stage of polymerization where there is a large amount of unreacted monomer components. The temperature of the refrigerant introduced into the reflux condenser can be appropriately selected depending on the monomer used, but the temperature of the refrigerant introduced into the reflux condenser is usually 45 to 180°C, preferably 80 to 150°C, and more preferably 100 to 130°C at the inlet of the reflux condenser. If the temperature of the refrigerant introduced into the reflux condenser is too high, the reflux amount decreases and the effect decreases. If the temperature of the refrigerant is too low, the efficiency of distilling off the monohydroxy compound tends to decrease. As the refrigerant, hot water, steam, heat transfer oil, etc. are used, and steam and heat transfer oil are preferred.
[0044] In order to maintain an appropriate polymerization rate and suppress distillation of monomers while not impairing the hue, thermal stability, light resistance, etc. of the final polycarbonate resin, it is important to select the type and amount of the above-mentioned catalyst. In producing a polycarbonate resin, if there are two or more reactors, the reactors may have a plurality of reaction stages with different conditions, or the temperature and pressure may be changed continuously.
[0045] In the production of polycarbonate resin, the catalyst can be added to a raw material preparation tank or a raw material storage tank, or can be added directly to a reactor. From the viewpoint of supply stability and control of melt polymerization, it is preferable to install a catalyst supply line in the raw material line before supplying to the reactor and supply the catalyst in the form of an aqueous solution. In the early stage of polymerization, it is preferable to obtain a prepolymer at a relatively low temperature and low vacuum. In the later stage of polymerization, it is preferable to increase the molecular weight to a predetermined value at a relatively high temperature and high vacuum. From the viewpoint of the hue and light resistance of the obtained polycarbonate resin, it is preferable to appropriately select the jacket temperature, the internal temperature, and the pressure in the reaction system at each molecular weight stage. For example, if either the temperature or the pressure is changed too quickly before the polymerization reaction reaches a predetermined value, unreacted monomers may be distilled out, which may upset the molar ratio of the dihydroxy compound and the carbonic acid diester, resulting in a decrease in the polymerization rate or making it impossible to obtain a polymer having a predetermined molecular weight or terminal group.
[0046] If the temperature of the transesterification reaction is too low, it will result in a decrease in productivity and an increase in the thermal history of the product, whereas if it is too high, it will not only result in the volatilization of the monomer but also may promote the decomposition and discoloration of the polycarbonate resin. In the production of polycarbonate resins, a method of subjecting a dihydroxy compound, including a first dihydroxy compound and a second dihydroxy compound, to an ester exchange reaction with a carbonate diester in the presence of a catalyst is usually carried out in a multi-stage process of two or more stages. From the viewpoint of increasing the molecular weight of the polycarbonate resin, narrowing the molecular weight distribution, and increasing the impact strength of the molded body, the first-stage transesterification reaction temperature (hereinafter sometimes referred to as "internal temperature") is preferably 140°C or higher, more preferably 150°C or higher, even more preferably 180°C or higher, and even more preferably 200°C or higher. From the viewpoint of improving the color of the molded body and making the molded body less susceptible to brittle fracture, the first-stage transesterification reaction temperature is preferably 270°C or lower, more preferably 240°C or lower, even more preferably 230°C or lower, and even more preferably 220°C or lower. The residence time in the first-stage transesterification reaction is usually 0.1 to 10 hours. From the viewpoint of increasing the molecular weight of the polycarbonate resin, increasing the impact strength of the molded body, and making the molded body less susceptible to brittle fracture, the residence time in the first-stage transesterification reaction is preferably 0.5 to 3 hours. The first-stage transesterification reaction is carried out while distilling off the generated monohydroxy compound out of the reaction system. The transesterification reaction temperature is increased from the second stage onwards, and the transesterification reaction from the second stage onwards is usually carried out at 210 to 270°C. From the viewpoint of increasing the molecular weight of the polycarbonate resin, increasing the impact strength of the molded body, improving the hue of the molded body, and making the molded body less susceptible to brittle fracture, the reaction temperature of the transesterification reaction from the second stage onwards is preferably 220 to 250°C. In the transesterification reaction from the second stage onwards, the pressure of the reaction system is gradually reduced from the pressure of the first stage while removing the generated monohydroxy compound from the reaction system, and the polycondensation reaction is usually carried out for 0.1 to 10 hours so that the pressure of the reaction system is finally 200 Pa or less. From the same viewpoint as the residence time in the first stage, the polycondensation reaction time from the second stage onwards is preferably 0.5 to 6 hours, more preferably 1 to 3 hours.
[0047] From the viewpoint of effective utilization of resources, it is preferable that the by-produced monohydroxy compound is purified as necessary and then reused as a raw material for carbonic acid diesters or various bisphenol compounds. From the viewpoint of further suppressing coloration, thermal deterioration, and discoloration of the polycarbonate resin and further improving the impact strength, the maximum temperature (internal temperature) in the reactor in all reaction stages is preferably less than 255°C, more preferably 250°C or less, and even more preferably 225 to 245°C.
[0048] In addition, from the viewpoint of increasing the molecular weight of the polycarbonate resin and increasing the impact strength, it is preferable to increase the polymerization temperature and extend the polymerization time as much as possible. On the other hand, if the polymerization temperature is increased or the polymerization time is extended, foreign matter and scorching are likely to occur, which tends to be disadvantageous from the viewpoint of brittle fracture. In order to achieve both further improvement of the impact strength and further suppression of brittle fracture, it is preferable to keep the polymerization temperature low, use a highly active catalyst for shortening the polymerization time, and adjust the pressure setting of the reaction system appropriately. Furthermore, it is also preferable to remove foreign matter and scorching generated in the reaction system by a filter or the like during the reaction or at the final stage of the reaction in order to further suppress brittle fracture.
[0049] In addition, when a polycarbonate resin is produced using a substituted diphenyl carbonate such as diphenyl carbonate or ditolyl carbonate as the carbonate diester represented by the formula (2), phenol or substituted phenol is by-produced, and it is difficult to completely avoid remaining in the polycarbonate resin. Since phenol or substituted phenol has an aromatic ring, it absorbs ultraviolet light, which may cause deterioration of light resistance, and may also cause odor during molding. After a normal batch reaction, the polycarbonate resin contains 1000 ppm by weight or more of aromatic monohydroxy compounds having an aromatic ring such as by-produced phenol. From the viewpoint of light resistance and odor reduction, it is preferable to reduce the content of aromatic monohydroxy compounds in the polycarbonate resin using a horizontal reactor with excellent volatilization performance or an extruder with a vacuum vent. The content of aromatic monohydroxy compounds in the polycarbonate resin is preferably 700 ppm by weight or less, more preferably 500 ppm by weight or less, and even more preferably 300 ppm by weight or less. It is difficult to completely remove aromatic monohydroxy compounds industrially, and the lower limit of the content of aromatic monohydroxy compounds in polycarbonate resins is usually 1 ppm by weight. Since these aromatic monohydroxy compounds may have a substituent in the raw material used, the aromatic monohydroxy compounds may naturally have a substituent, for example, an alkyl group having 5 or less carbon atoms.
[0050] In addition, Group 1 metals may be mixed in not only from the catalyst used but also from raw materials or reaction equipment. Among Group 1 metals, lithium, sodium, potassium, and cesium are likely to be mixed in, and sodium, potassium, and cesium are particularly likely to be mixed in. If these Group 1 metals are contained in large amounts in the polycarbonate resin, they may adversely affect the color. In order to fully avoid this, the total content of compounds containing these metals in the polycarbonate resin is usually 1 ppm by weight or less, preferably 0.8 ppm by weight or less, and more preferably 0.7 ppm by weight or less, in terms of the amount of metal.
[0051] The amount of metal in a polycarbonate resin can be measured by various known methods. For example, the metal in the polycarbonate resin can be recovered by wet ashing or the like, and then the amount of metal can be measured by atomic emission, atomic absorption, inductively coupled plasma (ICP), or the like. After the polycarbonate resin is melt-polymerized as described above, it is usually cooled and solidified, and then pelletized with a rotary cutter or the like.
[0052] The method of pelletization is not limited. For example, a method is adopted in which the polycarbonate resin is withdrawn in a molten state from the final polymerization reactor, cooled and solidified in the form of strands, and pelletized. Alternatively, a method can be adopted in which the resin is supplied in a molten state from the final polymerization reactor to a single-screw or twin-screw extruder, melt-extruded, cooled and solidified, and pelletized. Alternatively, a method can be adopted in which the resin is withdrawn in a molten state from the final polymerization reactor, cooled and solidified in the form of strands, pelletized once, and then supplied to a single-screw or twin-screw extruder again, melt-extruded, cooled and solidified, and pelletized.
[0053] In the extruder, residual monomers may be removed under reduced pressure, and a heat stabilizer, neutralizing agent, ultraviolet absorber, release agent, colorant, antistatic agent, slip agent, lubricant, plasticizer, compatibilizer, flame retardant, etc. may be added to the resin and kneaded. Although it depends on the glass transition temperature and molecular weight of the polycarbonate resin, the melt kneading temperature in the extruder is preferably 150 to 300 ° C, more preferably 200 to 270 ° C, and even more preferably 230 to 260 ° C. By setting the melt kneading temperature to the lower limit or higher within the above range, the melt viscosity of the polycarbonate resin is lowered, the load on the extruder is suppressed, and the productivity is improved. On the other hand, by setting the melt kneading temperature to the upper limit or lower within the above range, the thermal degradation of the polycarbonate is suppressed, the molecular weight is improved, and the mechanical strength is improved. Furthermore, coloring, gas generation, generation of foreign matter, and even the generation of scorching can be prevented. It is preferable to install a filter in the extruder or at the extruder outlet to remove foreign matter and scorching.
[0054] When the target filtration accuracy is to remove 99% or more of foreign matter, the filter opening is preferably 400 μm or less, more preferably 200 μm or less, and even more preferably 100 μm or less.
[0055] When the melt-extruded polycarbonate resin is cooled and pelletized, it is preferable to use a cooling method such as air cooling or water cooling.
[0056] When producing a polycarbonate resin by melt polymerization, a phosphoric acid compound or a phosphorous acid compound can be added during polymerization in order to further prevent coloration. The phosphoric acid compound or the phosphorous acid compound can be used alone or in combination of two or more kinds. As the phosphoric acid compound, trialkyl phosphate such as trimethyl phosphate, triethyl phosphate, etc. is used. The amount of the phosphoric acid compound added is preferably 0.0001 mol % or more and 0.005 mol % or less, and more preferably 0.0003 mol % or more and 0.003 mol % or less, based on the total dihydroxy compounds to be reacted.
[0057] As the phosphorous acid compound, any of the following heat stabilizers can be selected and used. In particular, one or more of the following can be suitably used: trimethyl phosphite, triethyl phosphite, trisnonylphenyl phosphite, trimethyl phosphate, tris(2,4-di-tert-butylphenyl)phosphite, and bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite. The amount of the phosphorous acid compound added is preferably 0.0001 mol% or more and 0.005 mol% or less, and more preferably 0.0003 mol% or more and 0.003 mol% or less, based on the total dihydroxy compounds to be reacted.
[0058] The phosphoric acid compound and the phosphorous acid compound can be added in combination. In that case, the total amount of the phosphoric acid compound and the phosphorous acid compound added is preferably 0.0001 mol % or more and 0.005 mol % or less, and more preferably 0.0003 mol % or more and 0.003 mol % or less, based on the total amount of dihydroxy compounds to be reacted.
[0059] The polycarbonate resin thus produced may further contain one or more heat stabilizers in order to suppress a decrease in molecular weight during molding or to improve the color. Examples of such heat stabilizers include phosphorous acid, phosphoric acid, phosphonous acid, phosphonic acid, and esters thereof. Specific examples include triphenyl phosphite, tris(nonylphenyl)phosphite, tris(2,4-di-tert-butylphenyl)phosphite, tridecyl phosphite, trioctyl phosphite, trioctadecyl phosphite, didecyl monophenyl phosphite, dioctyl monophenyl phosphite, diisopropyl monophenyl phosphite, monobutyl diphenyl phosphite, monodecyl diphenyl phosphite, monooctyl diphenyl phosphite, bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite, 2,2-methylenebis(4,6-di-tert-butylphenyl)octyl phosphite, and the like. phosphate, bis(nonylphenyl)pentaerythritol diphosphite, bis(2,4-di-tert-butylenyl)pentaerythritol diphosphite, distearyl pentaerythritol diphosphite, tributyl phosphate, triethyl phosphate, trimethyl phosphate, triphenyl phosphate, diphenyl monoorthoxenyl phosphate, dibutyl phosphate, dioctyl phosphate, diisopropyl phosphate, 4,4'-biphenylenediphosphinic acid tetrakis(2,4-di-tert-butylphenyl), benzenephosphonic acid dimethyl, benzenephosphonic acid diethyl, benzenephosphonic acid dipropyl, and the like. Among various heat stabilizers, trisnonylphenyl phosphite, trimethyl phosphate, tris(2,4-di-tert-butylphenyl)phosphite, bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite, and dimethyl benzenephosphonate are preferably used.
[0060] The heat stabilizer can be added in an amount in addition to the amount added during melt polymerization. That is, after a suitable amount of a phosphorous acid compound or a phosphoric acid compound is added to obtain a polycarbonate resin, a phosphorous acid compound can be further added by the compounding method described later. This further improves transparency and heat resistance.
[0061] The content of these heat stabilizers is preferably from 0.0001 to 1 part by weight, more preferably from 0.0005 to 0.5 parts by weight, and even more preferably from 0.001 to 0.2 parts by weight, based on 100 parts by weight of the polycarbonate resin. <Physical properties of polycarbonate resin> Preferred physical properties of the polycarbonate resin are shown below.
[0062] (reduced viscosity) The degree of polymerization (number average molecular weight) of a polycarbonate resin is expressed by reduced viscosity. The higher the reduced viscosity, the higher the molecular weight. From the viewpoint of further improving mechanical strength, the reduced viscosity of the polycarbonate resin is preferably 0.30 dl / g or more, more preferably 0.35 dl / g or more, and even more preferably 0.40 dl / g or more. From the viewpoint of improving fluidity during molding and improving productivity, and from the viewpoint of preventing distortion and thermal deformation of a molded body, the reduced viscosity is preferably less than 0.70 dl / g, more preferably 0.65 dl / g or less, and even more preferably 0.62 dl / g or less. The reduced viscosity can be controlled, for example, by changing the type of catalyst or adjusting the polymerization conditions. For example, when the molecular weight is increased by adjusting the above-mentioned production conditions, the reduced viscosity tends to be higher, and when the molecular weight is decreased, the reduced viscosity tends to be lower. The method for measuring the reduced viscosity will be described later.
[0063] (Other additives) In addition to the additives described above, the polycarbonate resin may contain various well-known additives within the scope of the present invention, such as ultraviolet absorbers, light stabilizers, release agents, lubricants, antioxidants, impact modifiers, flame retardants, flame retardant assistants, hydrolysis inhibitors, antistatic agents, foaming agents, fillers, and dyes and pigments (i.e., colorants).
[0064] (UV absorber) The ultraviolet absorbing agent is not particularly limited as long as it is a compound having ultraviolet absorbing ability. The compound having ultraviolet absorbing ability includes organic compounds and inorganic compounds, and organic compounds are preferred from the viewpoint of easily securing affinity with polycarbonate resin and easily dispersing uniformly. The molecular weight of the organic compound having ultraviolet absorbing ability is not particularly limited, but is usually 200 or more, preferably 250 or more. In addition, the molecular weight is usually 600 or less, preferably 450 or less, more preferably 400 or less. Preferred ultraviolet absorbing agents include benzotriazole compounds, triazine compounds, benzoate compounds, salicylic acid phenyl ester compounds, cyanoacrylate compounds, malonic acid ester compounds, and anilide oxalate compounds. Among these, benzotriazole compounds, hydroxybenzophenone compounds, and malonic acid ester compounds are preferably used. These may be used alone or in combination of two or more. Examples of commercially available ultraviolet absorbents include Adeka STAB (registered trademark) LA-29 and Adeka STAB (registered trademark) LA-31 manufactured by ADEKA Corporation.
[0065] Specific examples of the benzotriazole compound include 2-(2'-hydroxy-3'-methyl-5'-hexylphenyl)benzotriazole, 2-(2'-hydroxy-3'-t-butyl-5'-hexylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-t-butylphenyl)benzotriazole, 2-(2'-hydroxy-3'-methyl-5'-t-octylphenyl)benzotriazole, 2-(2'-hydroxy-5'-t-dodecylphenyl)benzotriazole, 2-(2'-hydroxy-3'-methyl-5'-t-dodecylphenyl)benzotriazole, 2-(2'-hydroxy-5'-t-butylphenyl)benzotriazole, and methyl-3-(3-(2H-benzotriazol-2-yl)-5-t-butyl-4-hydroxyphenyl)propionate.
[0066] Examples of the hydroxybenzophenone compounds include 2,2'-dihydroxybenzophenone, 2,2',4,4'-tetrahydroxybenzophenone, and 2-hydroxy-4-octoxybenzophenone.
[0067] Examples of the malonic acid ester compounds include 2-(1-arylalkylidene)malonic acid esters and tetraethyl-2,2'-(1,4-phenylene-dimethylidene)-bismalonate.
[0068] Examples of triazine compounds include 2-[4-[(2-hydroxy-3-dodecyloxypropyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine, 2,4-bis(2,4-dimethylphenyl)-6-(2-hydroxy-4-isooctyloxyphenyl)-s-triazine, and 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-[(hexyl)oxy]-phenol (manufactured by Ciba-Geigy, Tinuvin (registered trademark) 1577FF).
[0069] Examples of the cyanoacrylate compounds include ethyl-2-cyano-3,3-diphenylacrylate and 2'-ethylhexyl-2-cyano-3,3-diphenylacrylate. Examples of oxalic acid anilide compounds include 2-ethyl-2'-ethoxy-oxalanilide (more specifically, Sanduvor VSU manufactured by Clariant Japan, for example).
[0070] Examples of the benzoate compounds include KEMISORB112, KEMISORB113, and KEMISORB114 manufactured by Chemipro Chemicals, and Tinuvin 120 manufactured by BASF. An example of the salicylic acid phenyl ester compound is EUSOLEX OS manufactured by Merck.
[0071] The content of the ultraviolet absorber is preferably 0.005 parts by weight or more, more preferably 0.01 parts by weight or more, and even more preferably 0.1 parts by weight or more, relative to 100 parts by weight of the polycarbonate resin. In this case, the weather resistance improvement effect due to the inclusion of the ultraviolet absorber is more sufficiently obtained. In addition, the content of the ultraviolet absorber is preferably 5 parts by weight or less, more preferably 3 parts by weight or less, and even more preferably 1 part by weight or less, relative to 100 parts by weight of the polycarbonate resin. In this case, the occurrence of poor appearance due to bleeding out of the ultraviolet absorber is more sufficiently suppressed.
[0072] (Light stabilizer) The light stabilizer is not particularly limited as long as it is a compound that has the ability to prevent oxidation degradation due to light. Examples of light stabilizers used in polycarbonate resins include bis(2,2,6,6-tetramethyl-4-piperidyl)carbonate, bis(1,2,2,6,6-pentamethyl-4-piperidyl)[[3,5-bis(1,1,-dimethylethyl)-4-hydroxyphenyl]methyl]butylmalonate, bis(2,2,6,6-tetramethyl-4-piperidyl)succinate, bis(2,2,6,6-tetramethyl-4-piperidyl)sebacate, 4-benzoyloxy-2,2,6,6-tetramethylpiperidine, 4-hexanoyloxy-2,2,6,6-tetramethylpiperidine, 4-oct ... Examples of the hindered amines include bis(2,2,6,6-tetramethylpiperidine, 4-stearyloxy-2,2,6,6-tetramethylpiperidine, bis(2,2,6,6-tetramethyl-4-piperidyl)diphenylmethane-p,p'-dicarbamate, bis(2,2,6,6-tetramethyl-4-piperidyl)benzene-1,3-disulfonate, bis(2,2,6,6-tetramethyl-4-piperidyl)phenylphosphite, tetrakis(2,2,6,6-tetramethyl-4-piperidyl)=1,2,3,4-butanetetracarboxylate, and tetrakis(1,2,2,6,6-pentamethyl-4-piperidyl)=1,2,3,4-butanetetracarboxylate. These agents may be used alone or in combination of two or more. Examples of commercially available light stabilizers include Adeka STAB (registered trademark) LA-52, LA-57, LA-63, LA-68, LA-72, LA-77G, LA-81, and LA-87 manufactured by ADEKA CORPORATION; and Tinuvin PA123, Tinuvin PA144, and Uvinul 4050FF manufactured by BASF.
[0073] The content of the light stabilizer is preferably 0.01 parts by weight or more, more preferably 0.05 parts by weight or more, relative to 100 parts by weight of the polycarbonate resin. In this case, the weather resistance of the polycarbonate resin is further improved. In addition, the content of the light stabilizer is preferably 3 parts by weight or less, more preferably 1 part by weight or less, and even more preferably 0.5 parts by weight, relative to 100 parts by weight of the polycarbonate resin. In this case, the occurrence of adhesion to the mold during injection molding is prevented, and the surface appearance of the molded body is improved.
[0074] (Antioxidants) As the antioxidant, any antioxidant commonly used for resins can be used. The amount of the antioxidant added is preferably 0.001 parts by weight or more, more preferably 0.002 parts by weight or more, and even more preferably 0.005 parts by weight or more, relative to 100 parts by weight of the polycarbonate resin. In this case, the antioxidant's antioxidant effect is more fully obtained. In addition, the amount of the antioxidant added is preferably 5 parts by weight or less, more preferably 3 parts by weight or less, and even more preferably 2 parts by weight or less, relative to 100 parts by weight of the polycarbonate resin. In this case, contamination of the mold during molding is suppressed, and the surface appearance of the molded product is improved. From the viewpoint of stability against oxidation and heat, phosphite-based antioxidants, sulfur-based antioxidants, and phenol-based antioxidants are preferred.
[0075] (Phosphite antioxidant) Examples of the phosphite antioxidant include triphenyl phosphite, tris(nonylphenyl)phosphite, tris(2,4-di-tert-butylphenyl)phosphite, tridecyl phosphite, trioctyl phosphite, trioctadecyl phosphite, didecyl monophenyl phosphite, dioctyl monophenyl phosphite, diisopropyl monophenyl phosphite, monobutyl diphenyl phosphite, monodecyl diphenyl phosphite, monooctyl diphenyl phosphite, bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite, 2,2-methylenebis(4,6-di-tert-butylphenyl)octyl phosphite, bis(nonylphenyl)pentaerythritol diphosphite, bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, distearyl pentaerythritol diphosphite, and the like. Among these, trisnonylphenyl phosphite, tris(2,4-di-tert-butylphenyl) phosphite, bis(2,4-di-tert-butylphenyl) pentaerythritol diphosphite, and bis(2,6-di-tert-butyl-4-methylphenyl) pentaerythritol diphosphite are preferably used. These compounds may be used alone or in combination of two or more.
[0076] (Sulfur-based antioxidant) Examples of sulfur-based antioxidants include dilauryl-3,3'-thiodipropionic acid ester, ditridecyl-3,3'-thiodipropionic acid ester, dimyristyl-3,3'-thiodipropionic acid ester, distearyl-3,3'-thiodipropionic acid ester, laurylstearyl-3,3'-thiodipropionic acid ester, pentaerythritol tetrakis(3-mercaptopropionate), pentaerythritol tetrakis(3-laurylthiopropionate), glycerol-3-stearylthiopropionate, bis[2-methyl-4-(3-laurylthiopropionyloxy)-5-tert-butylphenyl]sulfide, octadecyl disulfide, mercaptobenzimidazole, 2-mercapto-6-methylbenzimidazole, and 1,1'-thiobis(2-naphthol). Among these, pentaerythritol tetrakis(3-laurylthiopropionate) is preferable. These compounds may be used alone or in combination of two or more.
[0077] (Phenol-based antioxidant) Examples of phenol-based antioxidants include triethylene glycol-bis[3-(3-tert-butyl-5-methyl-4-hydroxyphenyl)propionate], 1,6-hexanediol-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], pentaerythritol-tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, phenyl)propionate, 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, 3,5-di-tert-butyl-4-hydroxy-benzylphosphonate-diethyl ester, tris(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanurate, 4,4'-biphenylenediphosphinic acid tetrakis(2,4-di-tert-butylphenyl), 3,9-bis{1,1-dimethyl-2-[β-(3-te rt-butyl-4-hydroxy-5-methylphenyl)propionyloxy]ethyl}-2,4,8,10-tetraoxaspiro(5,5)undecane, 2,6-di-tert-butyl-p-cresol, 2,6-di-tert-butyl-4-ethylphenol, etc. Among these compounds, aromatic monohydroxy compounds having one or more substituents consisting of an alkyl group having 5 or more carbon atoms are preferred. Specifically, octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, pentaerythritol-tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 1,6-hexanediol-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, etc. are more preferred, and pentaerythritol-tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] is even more preferred. These compounds may be used alone or in combination of two or more.
[0078] (Impact Modifier) The impact modifier is not particularly limited as long as it is an elastomer component that improves impact strength. From the viewpoint of excellent transparency, an elastomer having a core-shell structure is preferable. An "elastomer having a core-shell structure" is a core-shell type graft copolymer that is composed of an innermost layer (core layer) and one or more outer layers (shell layers) covering it, and a shell layer is formed around the core layer by graft copolymerizing a copolymerizable monomer component into the core layer. The elastomer having a core-shell structure is preferably a core-shell type graft copolymer in which a polymer component called a rubber component is used as the core layer and a monomer component copolymerizable with the core layer is graft copolymerized as a monomer for forming the shell layer. Examples of the core-shell type graft copolymer include "Paraloid (registered trademark) EXL2602", "Paraloid (registered trademark) EXL2603", "Paraloid (registered trademark) EXL2655", "Paraloid (registered trademark) EXL2311", "Paraloid (registered trademark) EXL2313", "Paraloid (registered trademark) EXL2315", "Paraloid (registered trademark) KM330", "Paraloid (registered trademark) KM336P", and "Paraloid (registered trademark) KCZ201" manufactured by Rohm and Haas Japan Co., Ltd.; Examples of such polymers include "Blen (registered trademark) C-223A," "Metablen (registered trademark) E-901," "Metablen (registered trademark) S-2001," "Metablen (registered trademark) W-450A," "Metablen (registered trademark) SRK-200," and Kaneka Corporation's "Kane Ace (registered trademark) M-511," "Kane Ace (registered trademark) M-600," "Kane Ace (registered trademark) M-400," "Kane Ace (registered trademark) M-580," "Kane Ace (registered trademark) M-590," "Kane Ace (registered trademark) M-591," and "Kane Ace (registered trademark) MR-01."
[0079] (Coloring agent) Examples of the colorant include organic pigments, organic dyes and pigments such as organic dyes, and inorganic pigments. The colorant may be used alone or in combination of two or more. Examples of inorganic pigments include oxide pigments such as titanium oxide, zinc white, red iron oxide, chromium oxide, iron black, titanium yellow, zinc-iron brown, copper-chromium black, and copper-iron black, as well as carbon black. Examples of organic dyes and pigments include condensed polycyclic dyes and pigments such as azo-based, thioindigo-based, perinone-based, perylene-based, quinacridone-based, dioxazine-based, isoindolinone-based, and quinophthalone-based; anthraquinone-based, perinone-based, perylene-based, methine-based, quinoline-based, heterocyclic, and methyl-based dyes and pigments; and phthalocyanine-based dyes and pigments. From the viewpoint of being able to maintain the image clarity provided by the colorant for a long period of time even when the molded article is used outdoors, the colorant is preferably an inorganic pigment. From the viewpoint of obtaining an original molded product with good image clarity, the amount of colorant added is preferably 0.05 parts by mass or more and 5 parts by mass or less, more preferably 0.05 parts by mass or more and 3 parts by mass or less, and even more preferably 0.1 parts by mass or more and 2 parts by mass or less, per 100 parts by weight of polycarbonate resin.
[0080] (Inorganic filler) In order to obtain a reinforcing effect, an inorganic filler can be added to the polycarbonate resin. From the viewpoint of obtaining a sufficient reinforcing effect and preventing deterioration of appearance due to the addition, the amount of the inorganic filler added is preferably 1 part by weight or more and 100 parts by weight or less, and more preferably 3 parts by weight or more and 50 parts by weight or less, per 100 parts by weight of the polycarbonate resin.
[0081] Examples of inorganic fillers include calcium silicates such as talc, mica, and wollastonite, as well as glass fibers, milled glass fibers, glass flakes, glass beads, carbon fibers, silica, alumina, titanium oxide, calcium sulfate powder, gypsum, gypsum whiskers, barium sulfate, carbon black, graphite, iron powder, copper powder, molybdenum disulfide, silicon carbide, silicon carbide fibers, silicon nitride, silicon nitride fibers, brass fibers, stainless steel fibers, potassium titanate fibers, whiskers, etc. Among these, glass fibrous fillers, glass powder fillers, glass flake fillers, carbon fibrous fillers, carbon powder fillers, carbon flake fillers, various whiskers, wollastonite, mica, and talc are preferred. More preferred are glass fibers, glass flakes, milled glass fibers, carbon fibers, wollastonite, mica, and talc.
[0082] [Molded body] <Forming method> Polycarbonate resins are processed into various molded articles by molding methods such as injection molding (insert molding, two-color molding, sandwich molding, gas injection molding, etc.), extrusion molding, blow molding, hollow molding, compression molding, etc. Among these molding methods, injection molding is preferred. The molded articles are used for medical purposes.
[0083] The medical molded body contains polycarbonate resin, and is a molded body made of, for example, polycarbonate resin. The medical molded body can accommodate a nucleic acid-containing substance, such as a nucleic acid drug, and is configured to have a contact surface with the nucleic acid-containing substance. The medical molded body has a contact surface with the nucleic acid-containing substance when used. The nucleic acid-containing substance accommodated in the medical molded body may be in the form of a solid (powder) or a liquid. From the viewpoint of making the nucleic acid adsorption suppression effect of the molded body more prominent, it is preferable that the nucleic acid-containing substance is a liquid.
[0084] Examples of nucleic acids include deoxyribonucleic acid (i.e., DNA), ribonucleic acid (i.e., RNA), antisense nucleic acid, siRNA, miRNA, miRNA antisense, miRNAmimic, CpG oligodeoxynucleotide, decoy nucleic acid, nucleic acid aptamer, and ribozyme.
[0085] <Physical properties of molded body> The molded article preferably has the following physical properties.
[0086] (Total light transmittance) From the viewpoint of improving the visibility of the contents in medical applications, the total light transmittance of the molded article is preferably 85% or more, more preferably 90% or more. The method for measuring the total light transmittance will be described later. The total light transmittance is controlled by adjusting the type and amount of the transesterification catalyst and the transesterification reaction temperature.
[0087] (Nucleic acid adsorption) From the viewpoints of minimizing the loss of drug solution, enabling accurate drug administration, and minimizing sample loss during testing, the amount of nucleic acid adsorbed on the molded product was set at 4.0 ng / mm 2 From the same viewpoint, the amount of nucleic acid adsorption is 3.5 ng / mm 2 It is preferable that the concentration is less than 3.0 ng / mm 2 More preferably, it is 2.0 ng / mm 2 More preferably, it is 1.5 ng / mm 2Even more preferably, it is 1.2 ng / mm 2 It is particularly preferable that the adsorption amount of nucleic acid is less than 100%. The smaller the value, the more preferable the adsorption amount of nucleic acid. The adsorption amount of nucleic acid of the molded article is controlled by adjusting the polymer composition constituting the polycarbonate resin. Specifically, the adsorption amount of nucleic acid tends to decrease by increasing the content ratio of the structural unit (A) represented by the above formula (1) or decreasing the content ratio of the structural unit (B). On the other hand, the adsorption amount of nucleic acid tends to increase by decreasing the content ratio of the structural unit (A) represented by the above formula (1) or increasing the content ratio of the structural unit (B). The method for measuring the adsorption amount of nucleic acid will be described later, and is carried out, for example, by real-time PCR.
[0088] The measurement of the amount of adsorbed nucleic acid is preferably carried out by RNA such as siRNA or mRNA. The RNA may be single-stranded or double-stranded. From the viewpoint that double-stranded RNA is more stable and easier to handle than single-stranded RNA, and that commercial products are easily available for research purposes, the measurement of the amount of adsorbed nucleic acid is more preferably carried out by siRNA.
[0089] (Application) The molded article is suitable for medical use because it can suppress the adsorption of nucleic acids and has excellent impact resistance, scratch resistance, and transparency. The shape of the molded article for medical use is preferably a vial, an ampoule, a tube, a syringe, or a bottle. The syringe is specifically a syringe excluding a needle. EXAMPLES
[0090] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples as long as the gist of the invention is not exceeded. In the following, the physical properties of the polycarbonate resin and the molded products were evaluated by the following methods.
[0091] "Measurement of reduced viscosity" A polycarbonate resin sample was dissolved in a solvent to prepare a polycarbonate resin solution with a precise concentration of 1.00 g / dL. The solvent used was a mixed solvent of phenol and 1,1,2,2-tetrachloroethane in a weight ratio of 1:1. The reduced viscosity was measured at a temperature of 30.0°C ± 0.1°C using an Ubbelohde type viscometer manufactured by Moritomo Rika Kogyo Co., Ltd. The transit time t0 of the solvent and the transit time t of the solution were measured, and the relative viscosity η was calculated from the values of t0 and t using the following formula (i). rel Calculate the relative viscosity η rel From the following formula (ii), the specific viscosity η sp In the formula (ii), η0 is the viscosity of the solvent. sp By dividing by the concentration c [g / dL] of the polycarbonate resin solution, the reduced viscosity η (η = η sp / c) was calculated. A higher reduced viscosity means a higher molecular weight. η rel =t / t0 (i) η sp =(η-η0) / η0=η rel -1 (ii)
[0092] [Evaluation of molded products] The evaluation of the molded body was carried out using the following test pieces.
[0093] "How to prepare test specimens" The polycarbonate resin pellets were dried at 90 to 100°C for 10 hours under a nitrogen atmosphere. Next, the dried polycarbonate resin pellets were fed into an injection molding machine (J75EII type manufactured by Japan Steel Works, Ltd.) and injection molded under conditions of a resin temperature of 240°C and a molding cycle of 40 seconds to prepare test pieces. As the test pieces, a sheet-shaped test piece with a width of 100 mm, a length of 100 mm, and a thickness of 2 mm, and a tube-shaped test piece with a volume of 2 ml were prepared.
[0094] "Measurement of total light transmittance" The total light transmittance of the sheet-like test piece was measured using a Nippon Denshoku Industries Co., Ltd. NDH-7000II under a D65 light source in accordance with JIS K7361.
[0095] "Impact test" A tube-shaped test piece with a volume of 2.0 mL was filled with 1.5 mL of water. With the bottom of the test piece facing vertically downward, the test piece was dropped from a height of 1.5 m onto a concrete floor. The appearance of the test piece after the drop was visually inspected and evaluated according to the following criteria. 〇: No cracks or chips ×: Cracks or cracks occur In Comparative Example 2 described later, the impact test was carried out using a vial bottle (Vialex (registered trademark) manufactured by Nipro Corporation) having a volume of 5.0 mL instead of the tube-shaped test piece having a volume of 2.0 mL.
[0096] "Scratch resistance" The scratch resistance was evaluated using a friction and wear tester, HEIDON Type-30, manufactured by Shinto Scientific. Gauze folded three times was attached to an abrasive (curvature R10, width 20 mm). The gauze surface attached to the abrasive was pressed against the sheet-like test piece, and the sheet was slid back and forth horizontally 100 times while applying a load of 4.9 N (sliding test). After that, the surface of the sheet-like test piece was visually observed and evaluated according to the following criteria. 〇: Scratches are not visible or are barely noticeable ×: Scratches are noticeable In Comparative Example 2 described later, scratch resistance was evaluated using a vial bottle (Vialex (registered trademark) manufactured by Nipro Corporation) having a volume of 5.0 mL instead of the sheet-like test piece.
[0097] "Evaluation of nucleic acid adsorption" The amount of nucleic acid adsorption was measured by real-time PCR. siRNA was used as the nucleic acid. Evaluation was performed by generating complementary DNA (i.e., cDNA) from siRNA by reverse transcription reaction, and performing real-time PCR using this cDNA to measure the amount of nucleic acid (specifically, the amount of nucleic acid adsorbed to the molded product). Specifically, the measurement was performed according to the following (1) to (6). (1) Process 1 Thermo SiRNA n272236 was dissolved in nuclease-free water to prepare a 0.1 nmol / ml SiRNA solution. 400 μL of this SiRNA solution was poured into a 2.0 mL tube-shaped test piece, and the test piece was left on ice for 20 minutes to allow the nucleic acid to be adsorbed onto the test piece. (2) Process 2 Next, 200 μL of the SiRNA solution in the tube-shaped test piece was taken and transferred to another tube-shaped test piece into which 200 μL of nuclease-free water was poured, to prepare a SiRNA solution with a concentration of 0.05 nmol / mL. The tube-shaped test piece containing the SiRNA solution was left on ice for 20 minutes to adsorb the nucleic acid. (3) Process 3 Next, 200 μL of the SiRNA solution in the tube-shaped test piece was taken and transferred to another tube-shaped test piece into which 200 μL of nuclease-free water was poured to prepare a SiRNA solution with a concentration of 0.025 nmol / mL. The tube-shaped test piece containing the SiRNA solution was left on ice for 20 minutes to adsorb the nucleic acid. (4) Reverse transcription reaction 5μL of the SiRNA solution obtained after each of steps 1 to 3 was collected in a PCR tube with a volume of 0.2mL, and 3μL of 5xRT Primer (specifically, Thermo 4390816) was added to the PCR tube to prepare a mixed solution. The mixed solution was heated at 85°C for 5 minutes and then further heated at 60°C for 5 minutes to perform a heat denaturation treatment to obtain a heat denatured solution. This heat denatured solution was cooled to 4°C. Next, 0.15μL of 100mM dNTPs (Thermo Fisher Scientific), 1μL of MultiScribe Reverse Transctriptase (Thermo Fisher Scientific), 1.5μL of 10x Reverse Transcription Buffer (Thermo Fisher Scientific) with a concentration of 50U / UL, and 0.19μL of RNase Inhibitor (Thermo Fisher Scientific) with a concentration of 20U / uL were mixed to obtain a mixed solution. This mixed solution was added to the heat denatured solution. The heat-denatured solution after addition was successively heat-treated at 16° C. for 30 minutes, 42° C. for 30 minutes, and 85° C. for 5 minutes to carry out a reverse transcription reaction. The resulting reaction solution was cooled to 4° C. (5) Real-time PCT 23.4μL of PCR Reaction Mixture (Thermo #444557) was added to a real-time PCR tube, and 1.6μL of the reaction solution obtained by reverse transcription was added and mixed. After mixing, real-time PCR was performed to quantify the amount of siRNA in the siRNA solution in each step 1 to 3. Bio-Rad's CFX96 Deep Well (790BR02389) was used as the real-time PCR device. The real-time PCR conditions were heating at 50℃ for 2 minutes and 95℃ for 20 seconds, followed by 40 cycles of 95℃ for 1 second and 60℃ for 20 seconds. FAM was selected as the detection fluorescence. (6) Calculation of adsorption amount Adsorption amount A N (Unit: ng / mm 2 ) is the measured value C of real-time PCR of the siRNA solution (0.1 nmol / mL siRNA solution) after adsorption in step 1 A(Unit: Cycle) and the measured value C of real-time PCR of the siRNA solution after adsorption in step 3 (0.025 nmol / mL siRNA solution) B (unit: cycle) based on the following formula (I). A N =C A ×0.25-C B (I)
[0098] The abbreviations used in the following examples are as follows: (Polycarbonate resin) A-1: isosorbide / 1,4-cyclohexanedimethanol=70 / 30 mol% copolymer polycarbonate (specifically, Durabio (registered trademark) D7340R manufactured by Mitsubishi Chemical Corporation), reduced viscosity: 0.420 dL / g A-2: isosorbide / 1,4-cyclohexanedimethanol=90 / 10 mol% copolymer polycarbonate (manufactured by Mitsubishi Chemical Corporation: Durabio (registered trademark) D9340R), reduced viscosity: 0.504 dL / g A-2: isosorbide / 1,4-cyclohexanedimethanol=50 / 50 mol% copolymer polycarbonate (manufactured by Mitsubishi Chemical Corporation: Durabio (registered trademark) D5380R), reduced viscosity: 0.615 dL / g A-4: Bisphenol A polycarbonate resin (Mitsubishi Engineering Plastics: Novarex (registered trademark) 7022J) B-1: Vialex (registered trademark) manufactured by Nipro Corporation (Vialex material: borosilicate glass manufactured by Nippon Electric Glass Co., Ltd.) C-1: UV absorber (ADEKA Corporation, Adeka STAB (registered trademark) LA-29) C-2: UV absorber (ADEKA Corporation, Adeka STAB (registered trademark) LA-31) D-1: Hindered amine light stabilizer (ADEKA Corporation, Adeka STAB (registered trademark) LA-77G) D-2: Hindered amine light stabilizer (ADEKA Corporation, Adeka STAB (registered trademark) LA-52)
[0099] [Example 1] Polycarbonate resin (A-1), ultraviolet absorber (C-1), and light stabilizer (D-1) were mixed to obtain the composition shown in Table 1 below, and extruded into a strand shape using a twin-screw extruder TEX-33 manufactured by Japan Steel Works, Ltd., which has one vent port, so that the resin temperature at the outlet was 250°C. At this time, the vent port was connected to a vacuum pump, and the pressure at the vent port was controlled to be 500 Pa. The extruded resin was cooled and solidified with water, and then pelletized with a rotary cutter. The above-mentioned various evaluations were carried out using the obtained polycarbonate resin pellets. The results are shown in Table 1.
[0100] [Example 2] The procedure was the same as in Example 1, except that the composition was changed as shown in Table 1. The results are shown in Table 1.
[0101] [Example 3] The procedure was the same as in Example 1, except that the composition was changed as shown in Table 1. The results are shown in Table 1.
[0102] [Comparative Example 1] The procedure was the same as in Example 1, except that the composition was changed as shown in Table 1. The results are shown in Table 1.
[0103] [Comparative Example 2] The comparative example was the same as Example 1, except that glass (B-1) was used instead of the polycarbonate resin as shown in Table 1. In Comparative Example 1, measurement of the total light transmittance was omitted.
[0104] [Table 1]
[0105] The polycarbonate resins of Examples 1 to 3 contain a structural unit (A) derived from a dihydroxy compound represented by formula (1) and a structural unit (B) derived from an aliphatic dihydroxy compound and / or an alicyclic dihydroxy compound, and when nucleic acid is adsorbed to a molded product, the nucleic acid adsorption amount is 4.0 ng / mm 2As can be seen from Table 1, the molded articles containing the polycarbonate resins of Examples 1 to 3 were able to sufficiently suppress the adsorption of nucleic acids, and were excellent in impact strength, scratch resistance, and transparency. Therefore, the molded articles containing the polycarbonate resins of Examples 1 to 3 are suitable for medical use. In addition, the polycarbonate resins of Examples 1 to 3 have structural units derived from isosorbide and are composed of plant-derived raw materials.
[0106] On the other hand, in Comparative Example 1, a bisphenol A type polycarbonate resin is used, and does not contain the structural unit (A) derived from the dihydroxy compound represented by formula (1) and the structural unit (B) derived from an aliphatic dihydroxy compound and / or an alicyclic dihydroxy compound. Therefore, the molded article of Comparative Example 1 had a high nucleic acid adsorption amount and an insufficient effect of inhibiting adsorption of nucleic acid. In addition, the molded article of Comparative Example 1 had insufficient scratch resistance and transparency. Comparative Example 2 is an example using glass, and had a high nucleic acid adsorption amount and an insufficient effect of inhibiting adsorption of nucleic acid. In addition, Comparative Example 2 also had insufficient impact resistance.
[0107] From the above results, it was found that a medical molded article containing a polycarbonate resin, in which the polycarbonate resin contains a structural unit (A) derived from a dihydroxy compound represented by formula (1) and a structural unit (B) derived from an aliphatic dihydroxy compound and / or an alicyclic dihydroxy compound, had a nucleic acid adsorption amount of 4.0 ng / mm 2 It is understood that the medical molded article described below is made from plant-derived raw materials, and can suppress the adsorption of nucleic acids, while providing a medical molded article that has excellent impact strength, scratch resistance, and transparency.
Claims
1. A medical molded article containing a polycarbonate resin, The polycarbonate resin contains a structural unit (A) derived from a dihydroxy compound represented by the following formula (1) and a structural unit (B) derived from an aliphatic dihydroxy compound and / or an alicyclic dihydroxy compound, The amount of nucleic acid adsorbed was 4.0 ng / mm 2 The medical molded article is as follows: 【Chemistry 1】
2. 2. The molded article for medical use according to claim 1, wherein the content of the structural unit (A) is 30 to 95 mol % based on all structural units derived from dihydroxy compounds in the polycarbonate resin.
3. The molded article for medical use according to claim 1 or 2, wherein the polycarbonate resin has a reduced viscosity of 0.30 dL / g or more and less than 0.70 dL / g.
4. The medical molded article according to claim 1 or 2, which has a shape of a vial, an ampoule, a tube, a syringe, or a bottle.
Citation Information
Patent Citations
Polysulfide composition
JP1989000159A
Biocompatible polymer as antithrombotic material
JP2014161675A
Biocompatible material, coating composition, coating film, and article
JP2021091908A